2012
DOI: 10.4038/jas.v7i1.4062
|View full text |Cite
|
Sign up to set email alerts
|

Substitutes Or Complements: Formal And Infomrl Credit Demand By Maize Farmers In Ashanti And Brong Ahafo Regions Of Ghana

Abstract: This study examines credit demand by maize farmers and analysed factors influencing their use of informal and formal credit. The analysis is based on data collected from a survey of 590 maize farmers in seven districts of Ashanti and Brong Ahafo Regions of Ghana during May-July 2010. Descriptive statistics, probit and bivariate probit models were used to analyse the data. The study revealed informal credit sources for maize farmers as relatives and friends, traders and private money lenders. Maize traders are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…In our discussion with CRDB Bank loan manager, he disclosed that currently they are no longer offering loans to paddy producers due high default rate averaged at 78 per cent. Awunyo-Vitor [10] has reported in his empirical studies that large rate of default has been a major problem in agricultural credit [37] study also verified this finding. They concluded that as loan interest rate is smaller, financing costs will decrease for loan-takers and loan repayment will be easier.…”
Section: Results Of the Logistic Regression Analysismentioning
confidence: 61%
See 1 more Smart Citation
“…In our discussion with CRDB Bank loan manager, he disclosed that currently they are no longer offering loans to paddy producers due high default rate averaged at 78 per cent. Awunyo-Vitor [10] has reported in his empirical studies that large rate of default has been a major problem in agricultural credit [37] study also verified this finding. They concluded that as loan interest rate is smaller, financing costs will decrease for loan-takers and loan repayment will be easier.…”
Section: Results Of the Logistic Regression Analysismentioning
confidence: 61%
“…The loan volume may be another issue to discuss. Awunyo [10] stated that the larger the loan size, the lower the probability of repayment default. A poorly designed lending program and improper implementation may lead to defaults [11].…”
Section: Background Informationmentioning
confidence: 99%